Advantages and Disadvantages of Dental Miniimplants - Ten Different Viewpoints - R. Šmucler; P. Barták (Czech Dental Chamber, 2012)
So-called dental miniimplants are fast spreading pre-prosthodontics method. Number of dentists offering this method grows as well as number of existing systems. But we feel quantitative and qualitative insufficiency of the reviewed literature as main limit for future development. The authors have more than a decade of personal experience with this technology. Chosen paper title implies still incomplete picture of the actual limits of this method. But we can briefly conclude: Mini implants are predictable modality increasing retention of removable dentures. They have tiny indications in long-term fixed prosthetics. According to small diameter they are limited both aes-thetically and mechanically compare to conventional implants. However, miniimplants have significant advantage in situations of limited alveolar ridge diameter and for patients with multiple contra-indications (anatomical, medical, financial, technical incapability of dentist) for conventional implants. Lover economic costs and shorter treatment time are most significant advantages, enabling access to implant treatment for wider range of dentists and patients. The article omits otherwise very successful application of this technology in orthodontics.